Good Public Theology is Twilight Theology. A Constructive Deconstruction of Public Theology - Thomas, Günter (International journal of systematic theology, 2026)
The article outlines the basic features of a good public theology that is inspired by Paul’s description of the situation of the church and Christians: ‘The night has passed, the day is not far distant’ (Rom 13:12). In his analysis of the present, the author identifies eight specific challenges of contemporary culture – challenges that have so far been insufficiently addressed by ‘public theologies’. In contrast to many primarily discursive ‘public theologies’, the author emphasises the multimediality of ‘a good public theology’ and outlines five so-called ‘public faces of faith’ as examples. In principle, the article argues in favour of a ‘good public theology’ that does not dissolve into rational ethics, but rather explores and elucidates God’s adventures with the world. In doing so, this theology risks remaining ‘theological theology’. In view of the vast landscapes of ‘forgetting God’ and scepticism, a good twilight theology would do well to encourage the church to publish its ‘conflict conversations with God’ and the promises of God that are still outstanding. This sharing of the conflicts manifested in lament is a paradoxical intervention in the doubting and sceptical cultural presence. Furthermore, the article argues in favour of addressing the professions in particular as sub-publics that shape the present.